HUBUNGAN AGAMA DAN NEGARA DI INDONESIA - Dahlan, Moh (Universitas Islam Negeri Raden Intan Lampung, 2014)
RELIGION AND STATE RELATIONS IN INDONESIA: The relationship between religion and the state has become the actual and dynamic discourse in every phase of the civilization development, both in the West and the East. The discourse mainly focuses on the form of the state whether integral, symbiotic or secular. Departing from the discourse, this study examines the relationship between religion (Islam) and the state in Indonesia. The approach used is Martin Heidegger’s hermeneutics, while the assessment method used is the comparative method. The results of this study indicate that the Prophet, historically and normatively, had formulated the Medina State based on the Medina Charter which its spirit was based on the Qur’an, not based on the Quran literally. By the same line, the Muslim scholars who became the founder of the Indonesian State had also formulated Pancasila- as it was set forth in the Preamble of the NKRI’s 1945 Constitution – as an ideal foundation in establishing the dynamic and dialectical relationship between religion and state in Indonesia. The substance of religious norms was applied after the promulgation of, and in accordance with, Pancasila and the NKRI’s 1945 Constitution. The relationship between religion and the state, therefore, can be built based on the symbiotic or dynamic-dialectical typology.